THE EFFECT OF RETURN ON EQUITY AND DEBT TO EQUITY RATIO ON EARNINGS PER SHARE IN REAL ESTATE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - EVA PURNAMASARI; KURNIAWAN SURYATAMA (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2021)
This study aims to determine if the profitability ratios represented by Return on Equity (ROE) and the solvency ratios defined by the Debt to Equity Ratio (DER) have an impact on Earnings per Share (EPS) for real estate companies listed on the Indonesia Stock Exchange securities in 2019-2021. The population in this study were all property and real estate sector companies listed on the Indonesia Stock Exchange (IDX). In contrast, the sample in this study was 49 companies selected using a purposive sampling technique. The analysis model used in this study is a multiple linear regression analysis models, and the analysis technique uses the partial significance test, f test, and coefficient of determination. The results showed that the debt-to-equity ratio does not significantly affect earnings per share. In comparison, the return on equity variable positively and significantly affects earnings per share.